Identification of host-plant volatiles and characterization of two novel general odorant-binding proteins from the legume pod borer, maruca vitrata fabricius (lepidoptera: Crambidae) - Zhou J. (Public Library of Science, 2018)
10.1371/journal.pone.0141208